The Effect of Papain Enzymes and Probiotic Addition on Feed Towards The Catfish Growth Performance, Feed Utilization Efficiency and Survival Rate in Biofloc Techniques - Hidayatiningtyas, Kumala; Bintari, Siti Harnina; Iswari, Retno Sri (Proceeding International Conference on Science and Engineering, 2020)
The success of catfish farming (Clarias sp.) is influenced by feed and water quality. The low feed utilization results in high feed production costs. Alternative use of feed using the enzyme papain and probiotics, the papain enzyme is able to hydrolyze proteins into peptides to increase the utilization of protein in feed by the body. In addition, increased digestibility is done by the addition of probiotic bacteria such as Lactobacillus sp., Saccharomyses sp., Azotobacter sp., Streptomyces sp., Aspergillus sp., Trichoderma sp. into food that can increase feed digestibility and nutrient absorption. Water quality is one of the factors that caused a low survival rate of fish. Biofloc technology utilizes microbial activity that can convert organic waste intensively to form a flock that used by fish as a food source. This study aims to examine the effect of papain and probiotics enzyme addition in feed towards the growth, efficiency of feed utilization and survival rate of catfish using biofloc techniques. The research used a Completely Randomized Design (CRD) by five treatments using biofloc maintenance media and five treatments using non-biofloc, each repeated three times. This research used catfish with a density of 1 head /L kept for 4 weeks as a test animal, treatment P0 (test feed 0.0 gr / kg papain enzyme and 0 mL probiotics), P1 (test feed 0.25 gr / kg papain enzyme and 1 mL probiotic), P2 (Test feed 0.25 gr / kg papain enzyme and 2 mL probiotics), P3 (Test feed 0.5 gr / kg papain enzyme and 1 mL probiotic), P4 (Test feed 0.5 gr / kg of papain enzyme and 2 mL probiotics). The results showed that the addition of the papain and probiotics enzyme in feed with the best dosage was P2 with biofloc maintenance media that gave a real effect (P <0.05) on the efficiency of feed utilization and survival, but had no significant effect (P> 0.05) on growth of catfish (Clarias sp.). Water quality in the maintenance media is in a decent range for the maintenance of test fish.